Castilla y León en democracia : partidos, elecciones y personal político (1977-2007) / Mariano González Clavero, José-Vidal Pelaz López, Pablo Pérez López - Pelaz López, José-VidalPérez López, Pablo (1961-); González Clavero, Mariano
Fuentes y bibliografía: p. 335-345